A multivariate analysis of adverse childhood experiences and health behaviors and outcomes among college students. Issue 4 (19th May 2018) - Windle, Michael; Haardörfer, Regine; Getachew, Beth; Shah, Jean; Payne, Jackie; Pillai, Dina; Berg, Carla J.
ABSTRACT: Objective : This study investigated associations between adverse childhood experiences (ACE) prior to age 18 years and multiple health behaviors (eg, cigarette and other substance use) and outcomes (eg, obesity, depression) for a large college sample.Participants : 2, 969 college students from seven universities in the state of Georgia were included in the analysis.Methods : Web-based surveys were completed by students (45–60 minutes) during the spring semester, 2015.Results : Findings indicate that more ACEs are associated with higher levels of depressive symptoms, ADHD symptoms, cigarette use, alcohol use, marijuana use, and BMI, in addition to lower levels of fruit and vegetable intake, and sleep.Conclusion : ACEs may carry forward in the lifespan to influence a range of unhealthy outcomes among college students. College intervention programs may benefit by recognizing the pervasiveness of ACEs and their associations with health behaviors and outcomes, and include interventions across more than one health behavior.